Learning your limits: Nurses' experiences of caring for young unaccompanied refugees in acute psychiatric care. (15th December 2021) - Gabrielsson, Sebastian; Karim, Hannan; Looi, Git‐Marie Ejneborn
Abstract: Young unaccompanied refugees come in contact with acute psychiatric care due to pre‐existing mental health conditions as well as stressful and traumatic experiences before, during, and after migration. Previous research on nurses' experiences of caring for refugees has primarily reported on difficulties related to cultural differences and communication and how nurses might distrust refugees. This study aimed to describe registered nurses' experiences of caring for young unaccompanied refugees in acute psychiatric care. Semi‐structured interviews with ten nurses were analysed using a method for qualitative content analysis. Data were collected in Sweden during 2019 and 2020. Results describe nurses' experiences of caring for young unaccompanied refugees in acute psychiatric care in one theme: learning your limits and three sub‐themes: feeling powerless but doing what you can; taking a stance in a politicized environment; and being frustrated and in need of support . Findings highlight the potential and limitations of mental health nursing, the importance of reflection and peer support, and the importance of viewing the roles and responsibilities of mental health nurses and nursing in a societal context. These findings suggest that nurses can make a difference for young unaccompanied refugees in acute psychiatric care. However, in doing so, nurses need support in realizing what they can and cannot achieve. The study is reported in accordance with the COREQ guidelines.